Manajemen Komunikasi Dalam Upacara Maturan Jagung Meladung Di Banjar Saren, Desa Pakraman Mujaning Tumeling, Batumadeg Kabupaten Klungkung - I Nyoman Suartawan (Kamaya: Jurnal Ilmu Agama, 2018)
Implementation of Maturan Jagung Meladung ceremony is done in various temples in Banjar Saren, Pakraman Village Mujaning Tumeling so praying takes one day. Means of upakara in each temple is chosen based on the order of the general book of krama Banjar Saren Pakraman Mujaning Tumeling Village. Worship begins at Pancuhan Temple and then to Pura Pengujanan continued in three temple locations among Pura Dalem, Pura Griya and Pura Kamulan Kawitan meeting held at the last three temple locations accompanied by Baluh Tabuhur and Renteng dance.